Insulin resistance and inflammatory activation in older patients with systolic and diastolic heart failure. Issue 1 (16th December 2004) - Wisniacki, N; Taylor, W; Lye, M; Wilding, J P H
Abstract : Objective: To evaluate insulin resistance and systemic inflammation in older patients with systolic (SHF) or diastolic heart failure (DHF). Patients: 52 non-diabetic patients (> 70 and < 90 years old) with chronic heart failure (CHF) and hospitalised within the previous six months for heart failure were studied, together with a control group of older healthy volunteers (n  =  26). On the basis of Doppler echocardiographic criteria patients were classed as having SHF (n  =  27) or DHF (n  =  25). Main outcome measures: Fasting glucose, insulin, C reactive protein, interleukin 6, and tumour necrosis factor α soluble receptor II (TNF-αSRII) concentrations were determined. Insulin resistance was estimated by the homeostasis model assessment (HOMA). Results: HOMA index (median, interquartile range) was higher in patients with DHF (1.77, 1.06–2.26) than in patients with SHF (0.97, 0.81–1.85) or healthy volunteers (1.04, 0.76–1.44; p  =  0.01). After adjustment for body mass index, age, and use of angiotensin converting enzyme inhibitors, both groups of patients with CHF were more insulin resistant than were healthy volunteers (p  =  0.02). C reactive protein, interleukin 6, and TNF-αSRII were all significantly (p < 0.001) higher in patients with DHF and SHF than in healthy volunteers. All markers of systemic inflammation were independently associated with the presence of clinical CHF. Conclusion: Insulin resistance and inflammatory activation are present in older patients with SHF and DHF.